Research on the Generation Technology of Declared Airport Capacity Thresholds Based on Profit Maximization - Ying Liu; Zheng Zhao; Ying Peng (Aerospace)
Declared airport capacity is a key parameter in flight scheduling. The evaluation method for airport capacity primarily relies on computer simulation, and the capacity assessment results are dependent on the determination of the acceptable delay level. However, applying the same acceptable delay level across airports with different characteristics is unreasonable. To reasonably evaluate the acceptable delay level in simulations, this paper takes the flight profit of airport operations as the research object, conducting a marginal analysis of flight profit under various simulated delay levels. This approach identifies the simulated acceptable delay level that corresponds to maximum flight profit, serving as the threshold for assessing declared airport capacity. An empirical study is conducted using typical coordinated airports nationwide, aiming to determine acceptable delay level thresholds that align with declared airport capacity from an economic perspective. The experimental results indicate that the reasonable simulated acceptable delay levels for Shanghai, Nanjing, Shenyang, and Urumqi airports are 8.67 min, 6.18 min, 3.98 min, and 7.02 min, respectively. These levels demonstrate significant flight profit growth, validating the model’s positive role in enhancing the potential of declared airport capacity and in scientifically evaluating the supply-side capability of civil aviation.